Structural, civil and pipe drafting - Goetsch, David L. (Thomson/Delmar Learning, 2014)
This book helps the reader to develop the specific knowledge and skills needed to succeed in a rapidly evolving, high-demand field. This book opens with an overview of structural drafting - from department organization to product fabrication and shipping - before exploring critical topics such as structural steel, pre-cast concrete, and poured-in-place concrete